EXPLORING THE USE OF CHATGPT IN LANGUAGE LEARNING IN STUDENTS' WRITING SKILL - Aulia Rahma Salsabila; Monica Nila Sari; Christina Innocenti Tumiar Panggabean; Risa Triassanti (Universitas PGRI Ronggolawe Tuban, 2024)
ChatGPT interacts realistically and can answer follow-up questions, admit mistakes, challenge incorrect premises, and reject inappropriate requests. However, its use raises ethical and practical issues, such as the potential to increase inequalities in the educational system. This study aimed to determine the use and the impact of ChatGPT on students' writing abilities. The approach used in this research is a descriptive quantitative approach using a questionnaire. The findings showed that The participants mostly gave neutral responses in several questions, indicating that they use ChatGPT passively. However, in other questions students gave positive and negative responses. Keywords: Artificial Intelligence, ChatGPT, Students’ Writing Learning